2012
DOI: 10.1111/j.1753-1411.2012.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Korean Welfare State Development with New Empirical Data and Methods

Abstract: Selecting Korea as one of the conceptually classified East Asian welfare states, this paper aims to empirically investigate the determinants of Korean welfare state development. Linking the research question with the lively discussion on welfare state in Korea that is taking place domestically, this paper also aims to examine whether the development of the Korean welfare state has been influenced by politics of the left or by industrialization with functionalistic perspectives. We conduct an analysis first by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
2
16
1
Order By: Relevance
“…However, results suggest that political determinants would probably represent the most important field for welfare development, due perhaps to the contention of Kim [13] that grouping subject Asian countries with some incoherent features among them would be a problem. This is in contrast to the findings of the following authors with regards to the following influential variables: Lin [14] modernization; Kim and Jung [15] modernization, globalization and power resources; Ahn and Baek [16], Rupp and Stapleton [17] feminist and market theories; Ahn and Lee [18] economic development and modernization; Park [19] effects of globalization and economic crisis; Croisant [20] demographic, economic and political trends; and Cristea et al [21] economic growth. Kaseke [2] studied the challenges of extending social security to the poor in an African perspective and found that one of the reasons why the coverage of formal social security systems is low is because the self-employed domestic workers and those employed in the informal sector are not participating in the scheme.…”
Section: Literature Reviewcontrasting
confidence: 53%
“…However, results suggest that political determinants would probably represent the most important field for welfare development, due perhaps to the contention of Kim [13] that grouping subject Asian countries with some incoherent features among them would be a problem. This is in contrast to the findings of the following authors with regards to the following influential variables: Lin [14] modernization; Kim and Jung [15] modernization, globalization and power resources; Ahn and Baek [16], Rupp and Stapleton [17] feminist and market theories; Ahn and Lee [18] economic development and modernization; Park [19] effects of globalization and economic crisis; Croisant [20] demographic, economic and political trends; and Cristea et al [21] economic growth. Kaseke [2] studied the challenges of extending social security to the poor in an African perspective and found that one of the reasons why the coverage of formal social security systems is low is because the self-employed domestic workers and those employed in the informal sector are not participating in the scheme.…”
Section: Literature Reviewcontrasting
confidence: 53%
“…There has been a considerable internationalization of research agendas, with a particular focus on East Asia (e.g. see Hwang ; Ahn and Lee ; Lin and Yi ; Hudson et al . ; Yu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Because the value of public social expenditure varies depending on the size of the economy, it is controlled in the analysis by the level of GDP. Although aggregate public social expenditure has been criticized as a proxy for welfare effort (Esping‐Andersen, ; Kühner, ), since Wilensky (, p. 23) defined social security spending of gross national product (GNP) as a social security effort, public social expenditure as a percentage of economic size (such as gross national income or GDP) has been used as a variable to measure the welfare effort of a country (Ahn & Baek, ; Ahn & Lee, ; Bonoli, , ; Hong, ). This method has been widely used because of high availability for comparative study (Hong, ; Jensen, ) (Tables and ).…”
Section: Methodsmentioning
confidence: 99%